Practicing Health Geography
XV, 206 p. 54 illus., 52 illus. in color.
Keywords: This volume uniquely presents case studies on health geography in Africa, and analyzes health practices in different African regions to illustrate a unified perspective to the geographies of health. The book describes various contemporary and traditional themes that have characterized the discipline of health geography, and uses its 13 case studies across 14 chapters to challenge the perceived dichotomy between health geography and medical geography among health researchers and practitioners. In 3 sections, the book provides readers with a comprehensive and interdisciplinary approach to understanding health geography in Africa. The first chapter introduces the major theories and perspectives in health geography, and how these characteristics apply to health geography practices in Africa. Section 1 discusses the different uses of space-based analyses in health geography, including geo-data infrastructures, geographies of disease burden, spatial epidemiology, spatially precise public health, and spatial access to health. Section 2 discusses the different uses of place-based analyses in health geography, including health representation, healthcare access, food allergies, and health determinants. Section 3 addresses how geography is incorporated into decision processes in Africa, and how policy planning shapes health-related interventions at the population and individual level. The case studies here discuss geo-enabling health records, health policy, public health planning, and mobile health geographies.